(untitled) (Bangladesh Agronomy Journal, 2015)
A study was conducted to determine the critical period of weed competition in transplant Aus rice for var. BRRI dhan27. Among the treatments, weed free condition, competition of weed for first 10, 20, 30, 40, 50, 60 and 70 days and weed free later on, unweeded condition, one weeding at 20 days after transplanting and one weeding at 40 days after transplanting, the unweeded control plots showed the poor performance result in case of maximum parameters where grain yield was reduced the highest percentage (38.54%). On the basis of cost benefit ratio it was observed that the critical period of crop weed competition extended up to 30 days after transplanting of aus var. BRRI dhan27. Bangladesh Agron. J. 2014, 17(1): 95-102